Al-Sharṭ al-Jazāʾī wa-Atharuhu fī ʿUqūd al-Istisnāʿ wa-al-Salam: Dirāsah Fiqhiyyah Iqtiṣādiyyah - El Hassen Sid Ahmed El Habib; Hamed Abdulkarem Hamed Al-Bazeli (UIN Raden Mas Said Surakarta, 2025)
This study examines the reality and application of the penalty clause in Istisna‘ and Salam contracts, clarifying its impact on contractual obligations, explaining the Islamic jurisprudential stance considering the nature of both contracts, and highlighting their similarities and differences. The study used the descriptive-analytical method to review juristic opinions and Sharia evidence and adopted the comparative method to analyze rulings and legal effects in Istisna‘ and Salam contracts. It found that the penalty clause is permissible in Istisna‘ contracts to ensure fulfillment of agreed specifications within the specified time, provided compensation is reasonable, not exaggerated, and for actual harm incurred. In Salam contracts, it is impermissible as it constitutes Riba al-Nasi’ah due to its relation to debt. The penalty clause is prohibited in Salam contracts but allowed in Istisna‘ under conditions of actual damage, adherence to terms, and reasonable compensation. Breaches in Salam can be addressed by cancellation or litigation. The study distinguished penalty clauses from earnest money (Arbun) and stressed the need for actual damage and conditions for enforcement.